Analysis Of Representative Ability By Using Guided Inquiry Learning Model In Review Of Gender Students In MTsN - Nurul Rafiqah Nasution; Wahyudin Wahyudin (IKIP Siliwangi, 2021)
Based on the results of PISA and TIMSS, the mathematical ability of Indonesian students is at the cognitive knowing level which is the lowest level. This study aims to analyze: (1) students' mathematical representative ability through, and (2) the difficulty of representative experienced by students in solving problems of representative ability. The method of this study is qualitative research. The results showed: (1) students with high representative ability in terms of male and female genders were able to present pictures to solve problems. Students with the ability to represent are being viewed from male students who have not been able to aspects of words or written texts. Whereas female students are not yet capable of aspects of visual representative and the written words. Students with low representative ability in terms of male gender have not been able to visual present images. Then, aspects of mathematical expressions and written words have not been able to make mathematical model and written words. (2) the difficulties experienced by male students in solving problems of representative ability experiencing difficulties in terms of principles, verbal aspects and procedural terms. While the female students experiences difficulties in terms of concepts, aspects of principles, aspects of verbal and procedural terms. The conclusion in this study: female students in the high ability category more than male students. In the medium ability category, male students more than female students. In the low ability category, female students more than male students.